PipeZK: Accelerating Zero-Knowledge Proof with a Pipelined Architecture - Zhang, Ye; Wang, Shuo; Zhang, Xian; Dong, Jiangbin; Mao, Xingzhong; Long, Fan; Wang, Cong; Zhou, Dong; Gao, Mingyu; Sun, Guangyu (48th IEEE/ACM International Symposium on Computer Architecture (ISCA), 2021)
Zero-knowledge proof (ZKP) is a promising cryptographic protocol for both computation integrity and privacy. It can be used in many privacy-preserving applications including verifiable cloud outsourcing and blockchains. The major obstacle of using ZKP in practice is its time-consuming step for proof generation, which consists of large-size polynomial computations and multi-scalar multiplications on elliptic curves. To efficiently support ZKP and make it more practical to use in real-world applications, we propose PipeZK, an efficient pipelined accelerator consisting of two subsystems to handle the aforementioned two intensive compute tasks. The first subsystem uses a novel dataflow to decompose large kernels into smaller ones that execute on bandwidth-efficient hardware modules, with optimized off-chip memory accesses and on-chip compute resources. The second subsystem adopts a lightweight dynamic work dispatch mechanism to share the heavy processing units, with minimized resource underutilization and load imbalance. When evaluated in 28nm, PipeZK can achieve 10x speedup on standard cryptographic benchmarks, and 5x on a widely-used cryptocurrency application, Zcash.